The Study of Work Engagement Role of the Positive Job Performance of the Workers “A Pilot Study in the College of Nursing - Misan University” - Abdalqadir Hameed, Sulaf; Jauad Kadhim, Wassan; khalaf Hussain, sajjad (International Journal of Psychosocial Rehabilitation, 2020)
The work engagement is considered as one of the most important issues in human resources management (HRM), which has a relationship with some variables that related to the behavior of employees in Business Organizations such as work absenteeism, move to part-time employment and work hard. The work engagement enhances job satisfaction of the worker and improves their performance in order to achieve the aims and success.